2018
DOI: 10.3389/fmicb.2018.00275
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Biomarkers Associated with Human Extra-Pulmonary Tuberculosis Clinical Strains and Symptoms

Abstract: Background: The primary site of infection for Mycobacterium tuberculosis (Mtb) is the alveolar macrophages. However, Mtb can disseminate into other organs and causes extrapulmonary tuberculosis (EPTB). The diagnosis of EPTB is challenging due to relatively inaccessible infectious sites that may be paucibacillary and with clinical symptoms varying by site that are similar to those seen in other diseases. Hence, we sought to identify the expression patterns of a variety of cytokines that may be specific to EPTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…The enhanced levels of IL-10 and TGF-β in the lungs of active tuberculosis patients demonstrate a weakened immune response to M. tuberculosis , and hence, a role in the pathogenesis and disease progression ( 54 , 55 ). VEGF was also found to be at a significantly higher level in tuberculosis patients with extrapulmonary tuberculosis (EPTB) than those with pulmonary disease ( 56 ). In our study, properdin and TSR4+5 seems to result in a marked elevation of VEGF after 48 h. Since our data also shows that mycobacteria have a reduced phagocytosis by macrophages, the resulting extracellular bacteria may be encouraged by VEGF to disseminate.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced levels of IL-10 and TGF-β in the lungs of active tuberculosis patients demonstrate a weakened immune response to M. tuberculosis , and hence, a role in the pathogenesis and disease progression ( 54 , 55 ). VEGF was also found to be at a significantly higher level in tuberculosis patients with extrapulmonary tuberculosis (EPTB) than those with pulmonary disease ( 56 ). In our study, properdin and TSR4+5 seems to result in a marked elevation of VEGF after 48 h. Since our data also shows that mycobacteria have a reduced phagocytosis by macrophages, the resulting extracellular bacteria may be encouraged by VEGF to disseminate.…”
Section: Discussionmentioning
confidence: 99%
“…Goyal et al, suggested that the serum level of circulating IFN-γ and the ratio of IFN-γ and IL-2 remarkably identified EPTB patients from healthy controls [ 13 ]. Our study showed that, of the seven markers analyzed IFN-γ, IP10, IL2R, TNF-α and CXCL9 distinguished pulmonary tuberculosis cases from health controls with AUC value of 0.813, 0.79, 0.74, 0.7 and 0.69 respectively( Figure 3 ).In another study, the plasma level of VEGF was demonstrated to be a biomarker for differentiating EPTB from non-extrapulmonary forms [ 24 ]. In this study, individual cytokine analysis using a non-parametric t-test and ROC curve revealed that IL10 and CXCL-9 were able to differentiate EPTB from PTB cases ( Figure 5 C,D and Figure 6 ).…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, the development of a rapid and noninvasive bioassay is essential for the diagnosis of tuberculosis infection status. Different studies have proposed that both individual and/or combined cytokines can act as potential biomarkers in differentiating PTB from LTBI [12,15,19,22,23] as well as for the detection of EPTB [13,14,24]. In this study, we employed RT-qPCR to analyze the relative gene expression of cytokines that were stimulated as a part of the bioassay for discriminating tuberculosis infection status, which offers a better advantage with increased sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…That notwithstanding, a different 6-marker biosignature showed the most promise when only the PTB patients were compared to individuals with ORD (Norway and South Africa combined). Previous work by Fortún et al highlighted no differences in biomarker concentrations between PTB and EPTB patients ( 33 ), whilst Ranaivomanana et al reported differences in only TNF-α and VEGF after macrophage stimulation ( 34 ). Furthermore, blood transcriptional signatures reflecting immune response in PTB and EPTB patients were similar across sites of disease with varying degrees of responses correlating to the presence or absence of symptoms in another study ( 35 ).…”
Section: Discussionmentioning
confidence: 94%